Morphological, karyological features and pollen morphology of endemic Psephellus pyrrhoblephara Boiss. from Turkey - Tasar, Neslihan; Hayta, Şükrü; Kıran, Yaşar; Bağcı, Eyüp (My University, 2014)
In this study, morphological, morphometrical, karyological and detailed pollen morphology of the endemic Psephellus pyrrhoblephara Boiss. was studied for the first time. In the morphologic study of the plant, some morphological and morphometrical features was observed and compared with the Flora of Turkey records. Karyogram and idiograms of the plant were also prepared. The chromosome number of Psephellus pyrrhoblephara was found as 2n = 30 and haploid karyotype formula 8m + 2sm +5M. Metaphase chromosome length ranging from 2.36 to 1.34 ?m and the total haploid chromosome length was 26, 16 ?m. The results of the light microscope investigation of the pollen revealed that they have radially symmetrica, iso-polar tricolporate, spheroidal type and exine ornamentation was also determined scabrate. The results were discussed with genus patterns.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Turkish endemic; Psephellus pyrrhoblephara; Pollen; Morphology; Karyotype